Reclaiming Indigenous systems of healing: experiences of disabled Māori of Māori-centric health service responses in Aotearoa New Zealand during the COVID-19 pandemic - Michael Roguski; Tara N. Officer; Gretchen Good; Karen McBride-Henry (BMC Health Services Research)
Abstract Background The impact of the pandemic on Indigenous and disabled people's access to healthcare has resulted in significant disruptions and has exacerbated longstanding inequitable healthcare service delivery. Research within Aotearoa New Zealand has demonstrated that there has been success in the provision of healthcare by Māori for their community; however, the experiences of tāngata whaikaha Māori, disabled Māori, have yet to be considered by researchers. Methods Underpinned by an empowerment theory and Kaupapa Māori methodology, this research explores the lived realities of tāngata whaikaha Māori or their primary caregivers. Twenty in-depth interviews gathered participants’ lived experiences, and a discursive lens was brought to the narratives of tāngata whaikaha Māori who have accessed, and received, culturally responsive healthcare services during the pandemic. Results Positive experiences accessing primary and secondary services were associated with Māori-centred healthcare and seamless engagement with support services that were founded upon the active dismantling of structural inequities and the prioritisation of Māori cultural values in their care delivery, inclusive of tino rangatiratanga (sovereignty), and mātauranga Māori (Māori knowledge). Conclusions This study provides a novel and solid foundation for comprehending how healthcare can be realigned to cater to the requirements of disabled Indigenous populations.